Determining Bilateral Strength Imbalances in Youth Basketball Athletes - Thomas, Christopher; Comfort, Paul; Dos’Santos, Thomas; Jones, Paul A. (International Journal of Sports Medicine, 2017)
The aims of this study were: 1) to compare the strongest (D) and weakest (ND) limbs in determining muscle strength asymmetry (MSA) ratios among various muscle strength qualities and 2) to determine the relationships among various muscle strength qualities. 17 youth male basketball athletes (age=17.5±0.8 years; height=187.1±9.4 cm; body mass=81.4±10.1 kg) participated in this study. Knee flexor and extensor strength at 60°·s−1 was assessed for both limbs with the use of isokinetic dynamometry. Other tests involved single-leg hop (SLH), countermovement jump (CMJ) and isometric mid-thigh pull (IMTP). Statistically significant differences (p<0.05; d=0.40-0.98) were found between D and ND limbs for all strength measures. Imbalance ratio of the IMTP was significantly related to those of SLH (r=0.75, p=0.01) whereas no significant relationships between D:ND ratios were found from all other tests. Percentage agreements of MSA ranged from 64.7–88.2% between muscle strength qualities. The findings provide support for the use of field tests to detect lower-limb strength imbalances. Future research should examine the effect of different asymmetry thresholds on percentage agreements to diagnose MSA and determine its relationship to athletic performance.
Keywords: asymmetry; isokinetics; hop tests; countermovement jump; mid-thigh pull